2001
DOI: 10.1111/j.1755-0238.2001.tb00188.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive growth of grapevines in response to nitrogen supply and rootstock

Abstract: Nitrogen fertiliser was applied at two rates (0 or 100 kg N/ha) to field-grown Müller-Thurgau grapevines grafted onto six rootstocks (Kober 5BB, Teleki 5C, Teleki 8B, Selection Oppenheim 4, Couderc 3309, Ruggeri 140). Half the nitrogen was applied four weeks pre-flowering and half at the end of flowering. Nitrogen supply reduced symptoms of inflorescence necrosis and improved fruit set, but increased bunchstem necrosis, Botrytis cinerea bunch rot and yield. This was associated with reduced grape sugar, higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
50
0
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 15 publications
2
50
0
7
Order By: Relevance
“…In Chardonnay, on the other hand, 140Ru reduced the yield potential by decreasing both cluster number and fruit set, but compensatory processes in other yield components masked this rootstock effect so that final yields were similar across all rootstocks and own-rooted vines. The yield-promoting influence of 3309C on Merlot and Syrah contrasts with a cool/humid-climate rootstock trial with Müller-Thurgau (Keller et al 2001a), in which 3309C decreased both berry number per cluster (an effect it shared with 140Ru) and berry weight. In other dry-climate field trials that included some of the rootstocks used in this study with irrigated Chardonnay , Syrah (Stevens et al 2010), Cabernet Sauvignon (Williams 2010), Malbec (Di Filippo and Vila 2011), or unirrigated Cabernet Sauvignon (Nuzzo and Matthews 2006), rootstock effects on yield and its components tended to be minor and, although sometimes significant, were often inconsistent between years.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In Chardonnay, on the other hand, 140Ru reduced the yield potential by decreasing both cluster number and fruit set, but compensatory processes in other yield components masked this rootstock effect so that final yields were similar across all rootstocks and own-rooted vines. The yield-promoting influence of 3309C on Merlot and Syrah contrasts with a cool/humid-climate rootstock trial with Müller-Thurgau (Keller et al 2001a), in which 3309C decreased both berry number per cluster (an effect it shared with 140Ru) and berry weight. In other dry-climate field trials that included some of the rootstocks used in this study with irrigated Chardonnay , Syrah (Stevens et al 2010), Cabernet Sauvignon (Williams 2010), Malbec (Di Filippo and Vila 2011), or unirrigated Cabernet Sauvignon (Nuzzo and Matthews 2006), rootstock effects on yield and its components tended to be minor and, although sometimes significant, were often inconsistent between years.…”
Section: Discussionmentioning
confidence: 66%
“…Rootstocks are also used for their resistance to or tolerance of nematodes, adverse soil conditions such as drought, waterlogging, high or low pH, or salinity, and their ability to influence vine vigor and fruit ripening (Currle et al 1983, Pongrácz 1983, Galet 1998, Whiting 2004. Although the compounds responsible for fruit composition are mostly determined by the genotype of the scion (e.g., Gholami et al 1995), rootstocks may alter fruit composition indirectly by influencing scion vigor, canopy configuration, yield formation, and nutrient uptake (Schumann 1974, Ruhl et al 1988, Keller et al 2001a, 2001b.…”
mentioning
confidence: 99%
“…Excess nitrogen leads to high vigor, increasing fruit yield and affecting juice composition (i.e., pH and concentrations of organic acids and esters), but may also create conditions favorable to disease such as bunch stem necrosis and Botrytis cinerea bunch rot (Keller et al 2001). Potassium defi ciency adversely affects ripeness, but excess berry potassium is detrimental to wine quality (Mpelasoka et al 2003).…”
mentioning
confidence: 99%
“…Several studies have reported that high nitrogen nutrition predisposes berries to GM infections (Keller et al, 2001;Mundy, 2008;Valdés-Gómez et al, 2008). High nitrogen promotes excessive vegetative growth and vigor, which enhance canopy density, thus generating a microclimate within the grape canopy that favors GM.…”
Section: Nutrition and Fertilizationmentioning
confidence: 99%
“…High nitrogen promotes excessive vegetative growth and vigor, which enhance canopy density, thus generating a microclimate within the grape canopy that favors GM. In addition, high nitrogen levels delay berry ripening, increase cluster compactness and reduce the thickness of the berry cuticle (Valdés-Gómez et al, 2008;Keller et al, 2001).…”
Section: Nutrition and Fertilizationmentioning
confidence: 99%